2018
DOI: 10.1155/2018/4298583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Electrical Stimulation of the Quadriceps and Diaphragm in Critically Ill Patients: A Pilot Study

Abstract: Background Deep and respiratory muscle disorders are commonly observed in critically ill patients. Neuromuscular electrical stimulation (NMES) is an alternative to mobilize and to exercise that does not require active patient participation and can be used on bedridden patients. Objective Evaluate the effectiveness of the NMES therapy in quadriceps versus diaphragm subjects in mechanical ventilation (MV). Methods Sixty-seven subjects in MV were included, divided into 3 groups: (a) control group (CG, n=26), (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
46
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 41 publications
7
46
2
4
Order By: Relevance
“…A total of 693 related studies were identified in the preliminary search, and 11 RCTs [ 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], including 576 patients, were finally included. A flow chart detailing the article screening process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 693 related studies were identified in the preliminary search, and 11 RCTs [ 13 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] ], including 576 patients, were finally included. A flow chart detailing the article screening process is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… Study(Author/Year) Country Number of cases (E/C) Participants Intervention measures Frequency/intensity Measurement E C Leite et al. [ 24 ] 2018 Indonesia 41/26 ≥18 years of age, and ≥24 h of MV duration NMES Routine nursing care 45 min per day on the quadriceps; Synchronized impulse at a frequency of 30 Hz. MRC score, MV duration, ICU length of stay, total length of stay, MIP, FSS-ICU, ADL, GCS score.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Após a extração dos dados, eles foram agrupados em tabelas para permitir a especificação dos itens para facilitar a análise comparativa dos estudos, favorecendo a identificação da variabilidade entre eles. , com duração de 45 minutos16 . nutos, utilizando uma frequência de 50 Hz , largura de pulso 500US, não descrevendo o tempo on e off utilizado, enquanto o grupo controle (n = 42) recebeu apenas fisioterapia convencional.…”
unclassified